2011
DOI: 10.1016/j.theriogenology.2011.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Timed embryo transfer programs for management of donor and recipient cattle

Abstract: Currently, timed ovulation induction and fixed-time artificial insemination (FTAI) in superstimulated donors and synchronization protocols for fixed-time embryo transfer (FTET) in recipients can be performed using GnRH or estradiol plus progesterone/progestin (P4)-releasing devices and prostaglandin F(2α) (PGF2α). The control of follicular wave emergence and ovulation at predetermined times, without estrus detection, has facilitated donor and recipient management. However, because Bos taurus cows have subtle d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0
19

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(88 citation statements)
references
References 36 publications
2
67
0
19
Order By: Relevance
“…However, embryos at 3 days and older are thought to be more resistant to heat stress than oocytes and early stage embryos. Several studies observed that ET can be applied to dairy herds to improve fertility compared with AI, particularly during the hot season of the year (Ambrose et al, 1999;Baruselli et al, 2011;Chebel et al, 2008). Therefore, ET is a strategy that bypasses the negative effects of heat stress during the periods of follicular development and early embryonic development.…”
Section: Discussionmentioning
confidence: 99%
“…However, embryos at 3 days and older are thought to be more resistant to heat stress than oocytes and early stage embryos. Several studies observed that ET can be applied to dairy herds to improve fertility compared with AI, particularly during the hot season of the year (Ambrose et al, 1999;Baruselli et al, 2011;Chebel et al, 2008). Therefore, ET is a strategy that bypasses the negative effects of heat stress during the periods of follicular development and early embryonic development.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Baruselli et al 2011, utilizing data from a large commercial herd in Brazil, showed that conception results can be increased in about ~8% (cooler months) to 20% (warmer months) percentage points with the use of ET when compared to AI (Fig. 4).…”
Section: Use Of Moet and Ivp In Dairy Herdsmentioning
confidence: 99%
“…Assuming no change in estrus detection rates at 60%, that represents at least some 7% increase in pregnancy rate results, or according to the Wisconsin model from the ReproMoney program, an extra $US140 dollars per cow per year, and yet not accounting for offspring with better genetics. The scenario for repeat-breeder cows in a comparison between AI and ET is even more dramatic, where conception results found by Baruselli et al 2011 increased in about 15 to 20% points, or using the same rationale, an extra 11% points in pregnancy results or $US220 dollars per cow per year.…”
Section: Use Of Moet and Ivp In Dairy Herdsmentioning
confidence: 99%
“…Thus, distinct hormonal treatments protocols are required for artificial insemination and superovulation (Baruselli et al, 2011).…”
Section: Introductionmentioning
confidence: 99%